Isolation of Beer-Spoiling Bacteria from Texas Craft Breweries. Issue 2 (3rd March 2020) - Goodman, Mary; Neal, Jack A.; Corsi, Aaron; Sirsat, Sujata A.
ABSTRACT: For craft brewers establishing their brands in a competitive marketplace, spoilage incidents due to microbial contamination can result in financial loss and damage to reputation. This study tested for the presence of beer spoilage bacteria produced in craft beer. Bacteria in 20% of the beers tested on advanced beer-spoiling medium (ABD) were demonstrated. A statistically significant relationship between breweries and the presence of bacterial growth on the ABD media plates was seen. Craft brewers who wish to continue producing high-quality beer may benefit from a quality management program that includes a preventive approach to detect the microbiological risks.